PARTISIPASI SOSIAL PEREMPUAN DALAM PEMBANGUNAN DESA LASIAI KECAMATAN SINJAI TIMUR KABUPATEN SINJAI - Risfaisal Risfaisal; Neng Sri Nuraeni (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract This study examines the social participation of women in the development of the village of Lasiai, East Sinjai Subdistrict, Sinjai District. The problem in this research is how the form of social participation of women in the development of the village of Lasiai and how the impact of social participation of women in the development of the village of Lasiai, East Sinjai Subdistrict, Sinjai District. The purpose of this study was to determine the forms of women's social participation in the development of Lasiai villages and to determine the impact of women's social participation in the development of Lasiai Village in the East Sinjai Subdistrict, Sinjai District. This type of research is a descriptive study with a qualitative approach. The informants in this study were the village head, village secretary, village head, PKK mother. Data collection was collected using observation techniques, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and drawing conclusions. Triangulation is used to explain the validity of the data that is with the data source. The results showed that the form of women's social participation in the development of the village of Lasiai was through the first three stages, namely the planning stage, that women were present in the deliberation meeting held with village officials, Second, the implementation stage by increasing empowerment as a program such as the Al-qur 'love program. and active standby village programs. Third, the participation monitoring phase aims to find out how the implementation of development programs will work, and the impact of women's social participation in village development is a) positive impacts, namely open thinking (education), the economy, and women's leadership b) negative impacts, namely labeling or the stereotype of society towards women.Abstrak. Penelitian ini mengkaji tentang partisipasi sosial perempuan dalam pembangunan desa lasiai kecamatan sinjai timur kabupaten sinjai. Masalah dalam penelitian ini adalah bagaimana bentuk partisipasi sosial perempuan dalam pembangunan desa lasiai dan bagaimana dampak partisipasi sosial perempuan dalam pembangunan desa lasiai kecamatan sinjai timur kabupaten sinjai. Tujuan penelitian ini adalah untuk mengetahui bentuk partisipasi sosial perempuan dalam pembangunan desa lasiai dan untuk mengetahui dampak partisipasi sosial perempuan dalam pembangunan desa lasiai kecamatan sinjai timur kabupaten sinjai. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Informan dalam penelitian ini adalah Kepala Desa, Sekertaris Desa, Kepala Dusun, Ibu PKK. Pengumpulan data dikumpulkan dengan teknik pengamatan (Observasi ), wawancara, dan dokumentasi. Teknik analisis data adalah reduksi data, penyajian data, dan penarikan kesimpulan. Trianggulasi yang digunakan untuk menjelaskan keabsahan data yaitu dengan sumber data. Hasil penelitian menunjukkan bahwa bentuk partisipasi sosial perempuan dalam pembangunan desa lasiai yaitu melalui tiga tahap yang pertama yaitu tahap perencanaan adalah perempuan hadir dalam kegiatan rapat musyawarah yang dilakukan bersama aparat desa, Kedua yaitu tahap pelaksanaan dengan meningkatkan pemberdayaan sebagai program seperti program cinta Al-qur’an dan program desa siaga aktif. Ketiga yaitu tahap pengawasan partisipasi ini bertujuan untuk mengetahui bagaimana pelaksanaan program pembangunan akan berjalan, dan Dampak partisipasi sosial perempuan dalam pembangunan desa adalah a) dampak positif yaitu pemikiran mulai terbuka (Pendidikan), perekonomian, dan kepemimpinan perempuan b) dampak negatif yaitu adanya pemberian label atau streotipe masyarakat terhadap perempuan.